American political history: a very short introduction - Critchlow, Donald T (Oxford University Press, 2015)
"American Political History : A Very Short Introduction captures the richness of American political history, focusing primarily on national politics. It explores the nature of the two-party system, key turning points in American political history, representative presidential and congressional elections, struggles to expand the electorate, and critical social protest and third-party movements"--Provided by publisher